The Differences of Food Waste in Animal Side Dishes Based on Garnish Giving - Mustakim Muskatim; Hapsari Sulistya Kusuma; Yuliana Noor Setiawati Ulvie (Universitas Islam Negeri Walisongo Semarang, 2018)
Food waste is one of the important indicators to find out the success of food service in a food organization in a hospital. The purpose of this study was to determine the differences in food waste on a treatment: serve with and without garnishes on diet serving in Rajawali room to patients 5A and 5B Dr. Kariadi Semarang hospital. This type of descriptive analytic study illustrates the differences in the weight of the food waste (staple food, animal and vegetable side dish) serve with and without garnishes. This study involved 36 respondents which were divided into 2 groups. The first group of 18 respondents received food served with garnishes, while the second group of 18 received with no garnishes. The garnishes given in the form of lettuce and tomatoes (rounded cut on animal side dishes). The food waste was weighed using a digital scale with an accuracy of 0.01 grams and the data was then analyzed using Mann-Whitney. The results showed the food waste in animal side dishes with garnishes was 9.9%. While the serving with no garnishes was 26.4%. It implies that the use of garnishes is able to reduce the food waste on animal side dishes by 16.5%. Based on the data analysis, it was obtained the p-value = 0.000, which indicating a significant difference on the average weight of the food waste which served with and without garnishes.